(untitled) (Bangladesh Journal of Pharmacology, 2017)
Out of entire cascade of technologies and strategies, Northern blot assay remains the most preferential approach for immediate and accurate evaluation of expressed RNA species. However, an abundance of tRNAs species under physiological conditions compared to other small RNAs makes it difficult to accurately evaluate their transcriptional alterations through traditional Northern blot assay. Here, we describe an efficient protocol for detecting subtle alterations in tRNA species in mammals by a modified Northern blot assay. This report also compares the chemical versus UV-based crosslinking of tRNA species to the surface of solid supports. Video Clip of Methodology: Detection of cytosolic tRNA in mammal by Northern blot analysis: 16 min 55 sec Full Screen Alternate